THE INFLUENCE OF B-35 DIESEL FUEL TESTING PARAMETERS ON THE EFFICIENCY AND PERFORMANCE OF DIESEL ENGINES - Irene Nindita Pradnya; Shendy Krisdayanti; Nurul Komariyah (CENDEKIA EKSAKTA, 2024)
The use of biodiesel as a mixture of diesel fuel has become one of the solutions to reduce dependence on fossil fuels and reduce greenhouse gas emissions. The B-35 diesel program, consisting of a mixture of 35% biodiesel with 65% diesel, is an initiative of the Indonesian government to realize more sustainable energy. This study aims to analyze various test parameters of B-35 diesel, including density (ASTM D 1298), viscosity (ASTM D 445), and residual carbon content (ASTM D 4350), and analyze their impact on diesel engine efficiency and performance. The test method is carried out by measuring density using a hydrometer, viscosity using a kinematic viscometer, and carbon residue by heating the sample at a temperature of 500°C. The results showed that the B-35 diesel mixture had a higher density (855,72 kg/m3) and viscosity (3,150 mm2/s) compared to pure diesel, which was 840 kg/m3 and 2,8 mm2/s, making the fuel injection process uniform. The residual carbon content of 0.14%, which is lower than pure diesel, which is 0.18%, helps reduce the potential for the formation of combustion residue buildup in the engine, thereby helping to maintain engine performance. Based on these results, the use of B-35 diesel can be a more environmentally friendly alternative and support the improvement of diesel engine performance. Keywords : biodiesel, diesel, efficiency, emissions, oil.